Análise limite de estruturas enrijecidas sob tensões iniciais - Ochoa Lopez, Rafael Avencio (1990)
A numerical tool for limit load determination in stiffened structures under initial stresses using simplified models is presented. Nonlinear material and initial stresses effects in spacial frame and triangular flat shell elements are considered. Several examples are analised to demonstrate the viability of these models in limit load determination.